Factors associated with fear of hypoglycaemia among the T1D Exchange Glu population in a cross-sectional online survey - Jingwen Liu; Jeoffrey Bispham; Ludi Fan; Jiat-Ling Poon; Allyson Hughes; Alicia Mcauliffe-Fogarty; Oralee Varnado; Beth Mitchell (BMJ Open)
Objectives Fear of hypoglycaemia (FoH) has been associated with suboptimal diabetes management and health outcomes. This study investigated factors associated with behavioural and emotional aspects of FoH among adults living with type 1 diabetes (T1D) mellitus.Design Cross-sectional study.Setting Online survey hosted on T1D Exchange Glu, an online community for patients living with T1D mellitus.Measures The Hypoglycaemia Fear Survey II-short form and the Hypoglycaemic Attitudes and Behaviour Scale were used to assess FoH. Multivariable regressions were performed on assessment scores.Results The study included 494 participants (mean±SD age 43.9±12.2 years, duration of T1D mellitus 16.6±16.8 years, self-reported glycosylated hemoglobin (HbA1c) 6.9%±0.8% (52±9 mmol/mol)), 63% men, 89% on insulin pump, 25% experienced a severe hypoglycaemic event in the last 6 months. Multivariable regression analyses showed higher anxiety, depression severity and diabetes distress were independently associated with FoH (all p<0.01). Longer diabetes duration was associated with lower FoH (p<0.01). Past experience with severe hypoglycaemia was associated with higher worry of hypoglycaemia (p<0.01) but not avoidance behaviour (ns).Conclusions These results highlighted the multifaceted nature of FoH, which warrants further discussion between providers and patients to uncover drivers of and actions required to reduce FoH and improve patient care and outcomes.